PELATIHAN PRAKTIK AFFLIATE MARKETING PASAR PLATFORM E-COMMERCE DALAM MENUNJANG PEREKONOMIAN MASYARAKAT KELURAHAN SIPANGE K, TUKKA, KABUPATEN TAPANULI TENGAH - Aritha Panggabean, Sriayu; Andrian Irsyan, Andrian; Zafril Abdi Nasution, Zafril Abdi; Azriadi Tanjung, Azriadi; Hendra Saputra , Hendra (Cattleya Darmaya Fortuna, 2025)
The objectives of this community partnership program (PKM) are (1) to understand Affiliate Marketing on E-Commerce Platforms, and (2) to train the people of Sipange Village in Affiliate Marketing on E-Commerce Platforms. The training method consists of three stages: (1) Preparation, (2) Implementation, and (3) Final Evaluation. The PKM partners are the community of Sipange Village, Tukka District, Central Tapanuli Regency. This program aims to enhance the community's understanding of Affiliate Marketing on E-Commerce Platforms and serve as motivation to improve their standard of living.